Estimation of Conditions the Realization of Democratic Mechanisms the Transformation of Society: Tearing Away and Social Dialog - Тetyana Calinescu; Ganna Likhonosova; Оlena Zelеnkо (Montenegrin Journal of Economics, 2018)
The aim of the research is an exposure and ground of formal aspects tearing away of those transformations, which take place today in Ukrainian society, and creations on this basis certain communication channels for development of social dialog in society. The subject of the research is a complex of conditions which are led to the failure realization the transformational mechanisms of democratic transformations in Ukrainian society, and to the emergence of tendencies the tearing away of a large part of the population, and also the identification of ways to eliminate with help of social dialog tools. The methods of research is methods of supervision and generalization, which can determinate in conditions of realization the socio-economic transformations; methods of expert research, which are use for determination of priority directions and valued referencepoints of country development; monographic analysis, what can use for determination of essence the socio-economic tearing away on principles of synergetic co-operation in the conditions of democratic transformations. It is also; using the systems approach for the ground of democratic mechanisms the socio-economic transformations and its consequences; methods of attribute evaluation, that are use for determination of intensity the socio-economic tearing away and possibility to input the communication connections with help of a social dialog; a structural and logical analysis, what can use at research of directions the socio-economic transformations; reflexive methods, which are use for the choice of ways the socioeconomic bringing in the conditions of realization the democratic mechanisms of state transformation.